The Old Nubian Texts from Attiri - van Gerven Oei, Vincent W.J.; Laisney, Vincent Pierre-Michel; Ruffini, Giovanni; Tsakos, Alexandros; Weber-Thum, Kerstin; Weschenfelder, Petra; van Gerven Oei, Vincent W.J.; Laisney, Vincent Pierre-Michel; Ruffini, Giovanni; Tsakos, Alexandros; Weber-Thum, Kerstin; Weschenfelder, Petra (Earth, Milky Way punctum books, 2016)
The Old Nubian Texts from Attiri is the first publication in the Dotawo: Monographs series. It presents heretofore unpublished material: an edition of a series of manuscripts discovered during the Aswan High Dam campaign at the site of Attiri, a rocky island in the Batn el-Hajjar region in Sudan, and does so in an innovative way, through an intensive collaboration of the editors under the name of the Attiri Collaborative. By bringing together their diverse backgrounds in linguistics, archeology, Bible studies, history, anthropology, and philology, the editors hope to have provided an example of a new model of collective manuscript editing and the results such collaboration can attain. The collection consists of 15 manuscript fragments that were all written in Old Nubian. Among these manuscripts special mention should be made of two parchment leaves from a codex dedicated to works on the Archangel Michael, a lectionary containing fragments from the Gospel of Matthew and the Second Letter to the Corinthians, as well as a rare letter written on a leather sheet.
English
Keywords: Nubian; Attiri; Sudan; epigraphy; Nubian Studies; archaeology